DESIGN OF ANTI-SLIP SHOES FOR 12 TON PALM OIL TRUCK WHEELS - Dani Tri Wahyudi; Deni Shidqi Khaerudini (SINERGI, 2020)
The rainy season will have a severe problem to the transportation sector (including heavy-duty trucks) in the off-road area in Indonesia, especially in areas that do not have permanent access roads (asphalt or concrete roads). For heavy vehicles, especially oil palm transport trucks will experience such obstacles, including slippage when crossing muddy dirt roads, and it will have an impact on the logistics delivery process. Therefore, it is necessary to design a support system, especially on the wheels, to reduce the risk of skidding or rolling on truck-type vehicles. In this work, the design of the anti-slip shoe wheels of the colt diesel double type truck (CDD) is used on the rear-wheel-drive as a tool for handling the slippage. In this design, the maximum traction factor of the wheels based on the calculation on the rolling resistance should be higher than 594 kg. The next step is to determine the value of soil cohesion and soil internal friction angle obtained from the previous studies. In this study, a calculation simulation was carried out to accomplish the design of the main components of the anti-slip of a truck wheel in the form of a traction rod fin. The design is namely U channel profile steel based on SNI 07-0052-2006 type U50, U65, and U80 with dimensions of the fin depth (z) are 3.8 cm, 4.2 cm, and 4.5 cm and length of 30 cm. The results show that the three types of U channel iron used for the anti-slip shoes are useful for freeing trucks from slippage with a total load of 12 tons. Thus, the truck will be safe when crossing the muddy roads with clay, muddy clay, and sandy loam under the following conditions: minimum cohesion number of 0.008 kg/cm2, minimum internal friction angle in the soil of 4.631°, and the maximum water content of 59.6%.